2016
DOI: 10.3727/096504016x14575597858609
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SASH1 Inhibits the Proliferation, Invasion, and EMT in Hepatocarcinoma Cells

Abstract: The SASH1 (SAM- and SH3-domain containing 1) gene, a member of the SLY (SH3 domain containing expressed in lymphocytes) family of signal adapter proteins, has been implicated in tumorigenesis of many types of cancers. However, the role and mechanism of SASH1 in the invasion and metastasis of hepatocarcinoma are largely unknown. In this study, we investigated the role and mechanism of SASH1 in the invasion and metastasis of hepatocarcinoma. Our results showed that SASH1 was lowly expressed in hepatocarcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…SASH1 encodes a scaffold protein involved in the toll-like receptor 4, TLR4 signaling pathway that regulates the cascade of cytokine production and endothelial cell migration in response to invading pathogens [39]. SASH1 is shown to be downregulated in breast cancer [40] and, when highly expressed, SASH1 can inhibit proliferation, invasion, and endothelial mesenchymal transition in other malignancies such as hepatocellular carcinoma and gastric cancer [41,42]. ZDHHC8P1 is upregulated and differentially expressed in two preeclamptic patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…SASH1 encodes a scaffold protein involved in the toll-like receptor 4, TLR4 signaling pathway that regulates the cascade of cytokine production and endothelial cell migration in response to invading pathogens [39]. SASH1 is shown to be downregulated in breast cancer [40] and, when highly expressed, SASH1 can inhibit proliferation, invasion, and endothelial mesenchymal transition in other malignancies such as hepatocellular carcinoma and gastric cancer [41,42]. ZDHHC8P1 is upregulated and differentially expressed in two preeclamptic patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that SASH1 is down‐regulated in tumours and that this expression is correlated with tumour grade and prognosis. SASH1 is down‐regulated in a number of cancers, including HCC, breast cancer, gastric cancer, etc . Consistently, in this study, SASH1 was underexpressed in the ESCC cell lines, suggesting that SASH1 might be a candidate tumour suppressor gene in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded protein has also been described as a potential tumour suppressor that negatively regulates the proliferation and aggressiveness of multiple cancer cells. He et al reported that the overexpression of SASH1 inhibits proliferation, invasion and epithelial‐mesenchymal transition (EMT) in hepatocarcinoma cells . SASH1 overexpression in lung cancer cells also inhibits the migration/invasion and the protein expression of cyclin D1, matrix metalloproteinase‐1 (MMP‐1), and MMP‐2 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that SASH1 downregulation is associated with tumor metastasis [3,5]. Other studies indicate downregulated SASH1 promotes metastasis of hepatoma carcinoma cells through Shh signal pathway [7].…”
Section: Introductionmentioning
confidence: 99%